+0  
 
0
54
1
avatar+230 

Let \(C\)  be the circle with equation \(x^2-6y-3=-y^2-4x\) . If (a,b) is the center of \(C\)  and \(r\)  is its radius, what is the value of a+b+r?

ant101  Mar 14, 2017
Sort: 

1+0 Answers

 #1
avatar+75333 
0

x^2 - 6y - 3 = -y^2 - 4x    rearrange as

 

x^2 + 4x + y^2 - 6y = 3      complete the square on x and y

 

x^2 + 4x + 4  +  y^2 -6y + 9  =  3 + 4 + 9     factor and simplify

 

(x + 2)^2  + (y - 3)^2  = 16

 

The center is  (-2, 3)   and the radius = 4

 

So  a + b + r   =   -2 + 3 + 4  =   5

 

 

cool cool cool

CPhill  Mar 14, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details